3D Filaments Based on Polyhydroxy Butyrate—Micronized Bacterial Cellulose for Tissue Engineering Applications - Celestino, Matheus F.; Lima, Lais R.; Fontes, Marina; Batista, Igor T. S.; Mulinari, Daniella R.; Dametto, Alessandra; Rattes, Raphael A.; Amaral, André C.; Assunção, Rosana M. N.; Ribeiro, Clovis A. [UNESP]; Castro, Guillermo R.; Barud, Hernane S. (MDPI, 2023)
In this work, scaffolds based on poly(hydroxybutyrate) (PHB) and micronized bacterial cellulose (BC) were produced through 3D printing. Filaments for the printing were obtained by varying the percentage of micronized BC (0.25, 0.50, 1.00, and 2.00%) inserted in relation to the PHB matrix. Despite the varying concentrations of BC, the biocomposite filaments predominantly contained PHB functional groups, as Fourier transform infrared spectroscopy (FTIR) demonstrated. Thermogravimetric analyses (i.e., TG and DTG) of the filaments showed that the peak temperature (Tpeak) of PHB degradation decreased as the concentration of BC increased, with the lowest being 248 °C, referring to the biocomposite filament PHB/2.0% BC, which has the highest concentration of BC. Although there was a variation in the thermal behavior of the filaments, it was not significant enough to make printing impossible, considering that the PHB melting temperature was 170 °C. Biological assays indicated the non-cytotoxicity of scaffolds and the provision of cell anchorage sites. The results obtained in this research open up new paths for the application of this innovation in tissue engineering.
Keywords: 3D printing; micronized bacterial cellulose; poly(hydroxybutyrate); scaffolds; tissue engineering